Hydrologic Signals and Surprises in U.S. Streamflow Records During Urbanization. Issue 9 (25th September 2020) - Bhaskar, A. S.; Hopkins, K. G.; Smith, B. K.; Stephens, T. A.; Miller, A. J.
Abstract: Urban development has been observed to lead to variable magnitudes of change for stormflow volume and directions of baseflow change across cities. This work examines temporal streamflow trends across the flow duration curve in 53 watersheds during periods of peak urban development, which ranged from 1939 to 2016. We used U.S. Geological Survey streamgage records combined with pre‐development and urbanization characteristics to identify 20 years for analysis in each urbanizing watershed. Each urbanizing gage was paired with a nearby reference gage representing climatic trends over the same time period. Results indicated that urbanization, as measured by housing density, did not homogeneously alter the flow duration curve. Urbanization led to widely variable trends in low flow, where half of the urbanizing gages had increasing flow at the 10th non‐exceedance percentile, and the other half had declining low flow. High flows generally increased in streams as the area urbanized. The largest increases in high flows were in streams in semi‐arid and arid areas. The largest urban flow changes had transformations in wastewater infrastructure, water supply infrastructure, and flood control facilities. Isolating flow changes due to urbanization from those of reference sites will serve to better identify and manage synergistic effects of urban development and climate change on flooding and water availability. Plain Language Summary: We analyzed water flows in 53 U.S. streams that drain areas with housing density increases of at least 40% over 20 years. Streams had periods of low and high flows within that time frame. Low flows went up in about half the streams and went down in the other half. The largest decreases in low flows were seen where septic systems were converted to municipal sanitary sewer systems. High flows generally increased in streams as the area urbanized. The largest increases in high flows were in streams in semi‐arid and arid areas. Using historical records of changes in streamflow can help predict future changes in flow with further urbanization and separate the effects of urban development on streamflow from those of reference conditions. Key Points: During urbanization, half of 53 urbanizing gages had increasing low streamflow The largest urbanizing flow trends were in watersheds with changes in water supply and wastewater infrastructure, or in arid watersheds Urbanization leads to widely varying and substantial changes in streamflow across the flow duration curve